2018
DOI: 10.1103/physrevlett.121.058301
|View full text |Cite
|
Sign up to set email alerts
|

Growing Critical: Self-Organized Criticality in a Developing Neural System

Abstract: Experiments in various neural systems found avalanches: bursts of activity with characteristics typical for critical dynamics. A possible explanation for their occurrence is an underlying network that self-organizes into a critical state. We propose a simple spiking model for developing neural networks, showing how these may "grow into" criticality. Avalanches generated by our model correspond to clusters of widely applied Hawkes processes. We analytically derive the cluster size and duration distributions and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 70 publications
(111 reference statements)
2
27
1
Order By: Relevance
“…We conjecture that the key difference is that doubly stochastic processes propagate the underlying firing rate instead of the actual spike count. Thus, propagation of the actual number of spikes (as e.g., in branching or Hawkes processes; Kossio et al 2018), not some underlying firing rate, seems to be integral to capture the statistics of cortical spiking dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…We conjecture that the key difference is that doubly stochastic processes propagate the underlying firing rate instead of the actual spike count. Thus, propagation of the actual number of spikes (as e.g., in branching or Hawkes processes; Kossio et al 2018), not some underlying firing rate, seems to be integral to capture the statistics of cortical spiking dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This raises an interesting question: how does the brain finally reset to a near-critical state after learning, so that another (new) memory can be consolidated? Our work here does not address this issue, but previous work by others has shown that neurons and networks in the brain have built-in homeostatic mechanisms which serves to recalibrate synaptic efficacies (see References [ 48 , 49 , 50 , 51 , 52 ]), a process that was proposed to happen also during development [ 53 ]. Thus, it could be that homeostatic plasticity together with reduced external input during sleep is sufficient to drive the system towards criticality, as shown by Zierenberg, J. et al [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to µ → 1, DMMs must showcase a critical branching process. In fact, in the limit of µ → 1, the Stirling approximation of the Borel distribution is proportional to S −3/2 , namely a scale-free distribution [19,20].…”
Section: Mean-field Analysismentioning
confidence: 99%